Cover feature: bowl shaped monodentate phosphines by condensation of Imidazole units with boranes - Schall, Helene; Fritz, Olaf; Schikora, Margot; Elias, Jana; Pritzkow, Hans; Wadepohl, Hubert; Enders, Markus (Zeitschrift für anorganische und allgemeine Chemie, 2018)
The cover picture shows a new class of chiral phosphine ligands bearing three imidazole units bridged by boranes. The bowl shaped, C3 symmetric molecules are obtained by a simple condensation procedure. The steric bulk of these monodentate ligands can easily be adjusted over a large range by the use of different chiral or achiral boranes. The ligand character is determined by the almost pure s‐character of the phosphorous lone‐pair, leading to very short metal‐P distances. Details are discussed in the article by Markus Enders, Helene Schall, and Olaf Fritz, et al. on page 630 ff.